2023
DOI: 10.1101/2023.08.31.555521
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Characterizing human postprandial metabolic response using multiway data analysis

Shi Yan,
Lu Li,
David Horner
et al.

Abstract: Analysis of time-resolved postprandial metabolomics data can enhance our knowledge about human metabolism by providing a better understanding of similarities and differences in postprandial responses of individuals, with the potential to advance precision nutrition and medicine. Traditional data analysis methods focus on clustering methods relying on summaries of data across individuals or use univariate methods analyzing one metabolite at a time. However, they fail to provide a compact summary revealing the u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(10 citation statements)
references
References 63 publications
(79 reference statements)
2
8
0
Order By: Relevance
“…No statistically significant BMI-related group difference is observed using the patterns extracted by the ACMTF model. Previously, analysis of fasting data in females using PCA showed a weak BMI group difference while the analysis of T 0 -corrected data using a CP model did not reveal any BMI-related component (Yan et al, 2023). Hence, we observe that when jointly analyzing these data sets, the dynamic part blurs the weak signal in the fasting data.…”
Section: Discussionmentioning
confidence: 49%
See 4 more Smart Citations
“…No statistically significant BMI-related group difference is observed using the patterns extracted by the ACMTF model. Previously, analysis of fasting data in females using PCA showed a weak BMI group difference while the analysis of T 0 -corrected data using a CP model did not reveal any BMI-related component (Yan et al, 2023). Hence, we observe that when jointly analyzing these data sets, the dynamic part blurs the weak signal in the fasting data.…”
Section: Discussionmentioning
confidence: 49%
“…In our analysis, we include 161 features 2 and 292 subjects (140 males, 152 females) as in (Yan et al, 2023). Yan et al have shown that BMI groups behave differently in terms of metabolic responses among males compared to females (Yan et al, 2023).…”
Section: Data Descriptionmentioning
confidence: 99%
See 3 more Smart Citations